Genomic data from King penguin ( Aptenodytes patagonicus ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The King penguin is the second largest species of penguin. They have a circumpolar range, breeding on the subantarctic islands at the northern reaches of Antarctica, South Georgia, and other temperate islands. They were heavily hunted for oil on Macquarie Island. King penguins appear to have suffered a major population declines, and 70% are expected to disappear in the next eighty years, however they are still considered as Least Concern by the International Union for Conservation of Nature (IUCN). We sequenced the genome of an adult King penguin from Fortuna Bay, South Georgia (provided by Tom Hart) to a depth of approximately 120x with short reads from a series of libraries with various insert sizes (250bp-20Kb). The assembled scaffolds of high quality sequences total 1.24Gb, with the contig and scaffold N50 values of 114.03Kb and 2.77Mb respectively. We identified 15195 protein-coding genes. ...